Ecological and intrinsic drivers of foraging parameters of Eurasian lynx at a continental scale - Oliveira, Teresa; Mattisson, Jenny; Vogt, Kristina; Linnell, John; Odden, John; Oeser, Julian; Premier, Joseph; Rodríguez-Recio, Mariano; Belotti, Elisa; Bufka, Ludek; Černe, Rok; Duľa, Martin; et al. (The Journal of animal ecology, 2025)
The estimation of foraging parameters is fundamental for understanding predator ecology. Predation and feeding can vary with multiple factors, such as prey availability, presence of kleptoparasites and human disturbance. However, our knowledge is mostly limited to local scales, which prevents studying effects of environmental factors across larger ecological gradients. Here, we compared inter-kill intervals and handling times of Eurasian lynx (Lynx lynx) across a large latitudinal gradient, from subarctic to the Mediterranean ecosystems, using a standardised dataset of predicted adult ungulate kills from 107 GPS-collared lynx from nine distinct populations in Europe. We analysed variations in these two foraging parameters in relation to proxies reflecting prey availability, scavengers' presence and human disturbance, to improve our understanding of lynx predation at a continental scale. We found that inter-kill intervals and handling times varied between populations, social status and in different seasons within the year. We observed marked differences in inter-kill intervals between populations, which do not appear to be driven by variation in handling time. Increases in habitat productivity (expressed by NDVI, used as a proxy for prey availability) resulted in reduced inter-kill intervals (i.e. higher kill rates). We observed less variation in handling (i.e. feeding) times, although presence of dominant scavengers (wild boars and brown bears) and higher human impact led to significantly shorter handling times. This suggests that kleptoparasitism and human disturbance may limit the energetic input that lynx can obtain from their prey. We also observed that the human impact on foraging parameters can be consistent between some populations but context-dependent for others, suggesting local adaptations by lynx. Our study highlights the value of large-scale studies based on standardised datasets, which can aid the implementation of effective management measures, as patterns observed in one area might not be necessarily transferable to other regions. Our results also indicate the high degree of adaptability of these solitary felids, which enables them to meet their energy requirements and persist across a wide range of environmental conditions despite the constraints imposed by humans, dominant scavengers and variable prey availability.
Keywords: stravovací zvyklosti; Predatory Behavior; prey availability; Food Chain; Ecosystem; handling time; predátorské chování; Female; Lynx; zvířata; Europe; human impact; roční období; ženské pohlaví; Male; Eurasian lynx; inter‐kill interval; Seasons; foraging; Animals; scavengers; mužské pohlaví; Feeding Behavior; Evropa; potravní řetězec; ekosystém